Крымская война 1853-1856: [для среднего школьного возраста] / Владислав Артемов - Артемов Владислав (История России, 2005)
Экземпляры: (20231204) / Инвентарный номер: 39629 / Цена: 56.54 / Сис.шифр: 63.3(2)47ср / Авт.знак: А 86 / ГРНТИ: 03 / ББК: 63.3(2)47ср